The influence of an inpatient dual diagnosis program on readmission rates - Mahomed, Tasneem (My University, 2013)
The aim of this study was to establish whether the management of dual diagnosis patients in an integrated psychiatric unit influenced relapse and readmission rates. A retrospective record review was conducted to illustrate the influence of an admission to the Dual Diagnosis Unit (DDU) at Sterkfontein Hospital (SFH) on readmission rates of patients. These results were compared to readmission rates of a matched standard care (SC) group. Statistical data analysis revealed a larger presence of schizophrenia in the SC group, likely explained by the DDU’s patient selection procedure. Though not significant, readmission rates in the DDU group were lower than in the SC group, even though substance use levels in the DDU group was higher. This demonstrates the potential positive impact of the DDU program. The findings presented in this paper warrant further investigation in assessing the effectiveness of a DDU, using a larger sample size.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Psychiatry Johannesburg, 2013
Keywords: Hospitals, Psychiatric; Patient Readmission